Students' Social Involvement in the Community: Satisfaction, Motivations and Long-Term Influences - Simonovich, Javier; Elisha, Ety; Alkalay, Sarit (Advances in Social Sciences Research Journal, 2019)
The objective of the current research was to examine the satisfaction derived from, motivations for and long-term effects of social activity in the community carried out by students under academic sponsorship. Participants were fifty-eight undergraduate students who had completed their BA degrees at the Max Stern Yezreel Valley College in Israel. During their studies, all participants took a course of social involvement in the community, aimed to benefit disadvantaged populations (children and adolescents at risk, and children, adolescents and adults with disabilities and special needs). Participants were asked to complete two questionnaires: one examining their motivations for engaging in volunteer social activity in the community, and the other examining the long-term influences of this activity. The findings show that most of the participants derived high satisfaction from their social activity. No significant correlations were found between satisfaction and motivation for community social activity (egoistic/altruistic/materialistic). The long-term influences of community social activity were expressed primarily in terms of achieving personal gains. In examination the correlations between different types of motivations and long-term effects of the social activity, it was found that each of the examined motives exerted a positive effect, with altruistic motive showing a certain advantage. We also found that women expressed higher satisfaction from their social activity in the community, compared to men. Research findings can serve as a basis for initial assessment of community social activity as carried out in an academic setting and can reinforce and encourage academic institutions in continuing to support such noteworthy activities.